Analysis of Connective Exocentric Phrases in the Soloraya.Solopos.Com News Article Title 'Boyolali Copper Businessman Killed Wednesday Night' - Esti Ningtyas; Yusni Khairul Amri (Britain International for Academic Research (BIAR-Publisher), 2024)
In Indonesian, the term phrase comes from English, namely phrase, which is sometimes called a phrase in Standard Indonesian Grammar. Various definitions of phrases show the important role of phrases in language. Exocentric phrases are combinations of words without containing the element